PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, KEPEMILIKAN, LABA RUGI, PROFITABILITAS DAN SOLVABILITAS TERHADAP AUDIT REPORT LAG - GRETA JUANITA JUANITA; RUTJI SATWIKO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The purpose of this study is to analyze the influence of company size, auditors, ownerships, profit or loss, profitability and solvability to audit report lag. This research focused on manufacturing companies listed in Indonesian Stock Exchange from 2007 until 2009. 372 sample selected from pusposive sampling method. The statistical used in this research was multiple regression. The result of this research shows that company size, ownerships, profit or loss, DER significantly influencing audit report lag.